Respuesta :

Answer:

The average rate of change is [tex]-4[/tex]

Step-by-step explanation:

we know that

the average rate of change using the graph is equal to

[tex]\frac{f(b)-f(a)}{b-a}[/tex]

In this problem we have

[tex]f(a)=f(1)=0[/tex]  

[tex]f(b)=f(3)=-8[/tex]

[tex]a=1[/tex]

[tex]b=3[/tex]

Substitute

[tex]\frac{-8-0}{3-1}=-4[/tex]

Answer:

The average rate of change of function is -4 in [1,3]

Step-by-step explanation:

The average rate of change for graphic quadratic function for the interval from x=1 to x=3

The average rate of change of a function is change y over change in x.

[tex]\text{Average rate of change of function}=\dfrac{f(b)-f(a)}{b-a}[/tex]

where,

a=1 and b=3

Using graph we will find f(1) and f(3)

f(3)=-8

f(1)=0

[tex]\text{Average rate of change of function}=\dfrac{f(3)-f(1)}{3-1}[/tex]

[tex]\text{Average rate of change of function}=\dfrac{-8-0}{2}=-4[/tex]

Hence, The average rate of change of function is -4 in [1,3]